The Role of Policies Governing Urban Land Development in Sari - masoumeh amiribesheli; Hossein Mojtaba zadeh Khanghahi (تحقیقات کاربردی علوم جغرافیایی)
Land is the most important factor in the physical development of cities; land management has now become one of the most important concerns and concerns of local governments. Also, the sprawling growth of cities has degraded the environment and natural resources around the cities. Meanwhile, due to inadequate and accelerated decision-making, some of the inner-city and inter-contextual capacity of cities for development or redevelopment has been overlooked by urban managers. Cities play an important role in the economic growth of each country, with nearly 60 percent of the GDP of developing countries being produced in cities. They are the main engines of the growth of each country's national economy. The present study attempts to investigate the decision-making patterns of urban land policies in the physical development of Sari. The type of research method is descriptive-analytical and it is of applied nature. The findings of the study indicate that the lack of a clear vision and consequently uncoordinated policies and institutions, centralized and non-cooperative decision making, and excessive tenure without the necessary institutional capacity are the most important reasons for the inefficiency of urban land management policy. Therefore, the appropriate model of government policy in urban land management is integrated urban land management based on clear and necessary vision formulation. Expressing a one-piece strategic policy, and delegating part of the government's powers to the lowest level of local institutions with more specific capacity building, government intervention in the four areas of land management, land use, taxation and construction must be consistent and consistent. Since the government does not have the institutional capacity to perform such verification, it is limited to policymaking and oversight to achieve the policy goals and fulfills part of its verification duties in each of the four domains whilst capacity building the necessary training courses. It moves step by step with the policies adopted to the lowest level of local institutions